A novel method for quanitifying comfort in child passengers demonstrates an association between child restraint comfort and errors in use of booster seats. (29th May 2017) - Fong, Cameron K.; Bilston, Lynne E.; Paul, Gunther; Brown, Julie
ABSTRACT: Objective : Misuse of child restraint systems is a widespread and long-standing problem impacting risk of injury and death in car crashes. Discomfort has been suggested as a causative factor for misuse, particularly in errors introduced by children while they use the restraints. However, the relationship between comfort and errors in use has never been studied. In this study we examine the reliability and sensitivity of a newly developed observational method for assessing comfort in children in vehicles. We then use this method to examine the relationship between comfort and errors in use of booster seats. Methods : A novel method was developed for assessing comfort by counting fidgeting and postural adjustment behaviors to derive a Discomfort Avoidance Behavior (DAB) score. The sensitivity of the DAB score was examined by observing children in four different seating conditions designed as "comfortable" and "uncomfortable" (Part 1). Paired-samples t -tests were used to compare differences in DAB between seating conditions. The reliability of the DAB score was assessed by calculating the intraclass correlation coefficient (ICC) between DAB scores recorded by different researchers. The association between comfort and correctness of use was examined by observing children using booster seats (Part 2). The association between DAB score and number of usage errors was tested using linear regression analysis. Participants were children ages 4–8 years. Fourteen children participated in Part 1 and 15 children in Part 2. Results : The DAB score was sensitive to changes in seat condition ( p < 0.01), and was repeatable between different researchers (ICC 0.98, 95% confidence interval [CI] 0.954–0.991). Increases in DAB were associated with increases in the number of use errors among children using booster seats (errors in use = 3.89 × DAB − 2.18, p < 0.0001). Conclusion : The DAB score is a reliable and valid measure of comfort of children in child restraints but could be improved by incorporating a measurement of postural positioning. Comfort, as characterized by fidgeting and postural adjustment behaviors, is associated with correct use of child restraints. The broader implication is that this confirms ergonomic design of child restraints as important for minimizing errors in use. There is a need for further study of the impact of specific restraint design features on comfort experienced by children.